A Source of a Different Color: Exploring the Influence of Three Kinds of Science Communication on Audience Attitudes Toward Research - Tong, Stephanie Tom; Vultee, Fred; Kolhoff, Sean; Elam, Allison B.; Aniss, Mostafa (Frontiers in Communication, 2019)
Though the contemporary media environment is filled with many different sources disseminating communications about science— including journalists, politicians and opinion leaders, and researchers—few studies have examined how messages about science communicated by different sources directly influence audience opinion about scientific research itself. This experiment (N = 170) used stimuli articles that reflected different presentation sources (3: political/public relations/researcher) and types of science research (2: “hard”/“soft”) to examine effects on people’s attitudes towards the featured research project’s (a) utility and (b) worthiness of federal grant funding, while controlling for individual differences in political attitudes and interest in science. Overall, political-source messages suppressed ratings of the project’s worthiness of funding and utility, and while messages from the researcher source produced greater utility ratings compared to the public relations source for soft science projects, this pattern was reversed for hard science research. Additionally, different sources influenced people’s comprehension of articles they read. We interpret these results within the larger landscape of science communication and conclude with brief practical recommendations for those engaging in science communication.